Connecting remote populations to public health: the case for a digital immunisation information system in Nunavut. Issue 1 (1st January 2017) - Wilson, Lindsay A.; Pakes, Barry; Murphy, Malia S. Q.; Atkinson, Katherine M.; Bell, Cameron; Wilson, Kumanan
ABSTRACT: Despite the best efforts of local healthcare workers and health officials, Nunavut, a large geographical region in Northern Canada, has struggled with outbreaks of vaccine-preventable diseases (VPD). We contend that the implementation of an immunisation information system (IIS) could strengthen prevention and response efforts to this and future outbreaks of vaccine-preventable diseases. Developing an IIS in Nunavut that builds on the existing CANImmunize infrastructure would reduce the cost and complexity of developing a new IIS, and allow Nunavut to benefit from the ongoing efforts to secure data on the CANImmunize platform. Such a system would enable the identification of individuals and subpopulations at highest risk of infection based on vaccine series completion and permit the exploration of the underlying causes of outbreaks in the territory through consideration of demographic and temporal factors. Confirmed high rates of vaccination in the context of an outbreak would indicate potential issues with vaccine efficacy while low rates of vaccination would suggest that efforts should be devoted to increasing vaccine coverage. This approach could also lay the foundation for infrastructure expansion to other remote and/or Indigenous communities where geographical and accessibility issues complicate health care utilisation and monitoring, both in Canada and internationally.